A 3D k‐space Fourier encoding and reconstruction framework for simultaneous multi‐slab acquisition. Issue 3 (2nd May 2019) - Dai, Erpeng; Wu, Yuhsuan; Wu, Wenchuan; Guo, Rui; Liu, Simin; Miller, Karla L.; Zhang, Zhe; Guo, Hua
Abstract : Purpose: To propose a novel 3D k‐space Fourier encoding and reconstruction framework for simultaneous multi‐slab (SMSlab) acquisition and demonstrate its efficacy in high‐resolution imaging. Methods: First, it is illustrated in theory how the inter‐slab gap interferes with the formation of the SMSlab 3D k‐space. Then, joint RF and gradient encoding are applied to remove the inter‐slab gap interference and form a SMSlab 3D k‐space. In vivo experiments are performed to validate the proposed theory. Acceleration in the proposed SMSlab 3D k‐space is also evaluated. Results: High‐resolution (1.0 mm isotropic) images can be reconstructed using the proposed SMSlab 3D framework. Controlled aliasing in parallel imaging sampling and 2D GRAPPA reconstruction can also be applied in the SMSlab 3D k‐space. Compared with conventional multi‐slab acquisition, SMSlab exhibits better SNR maintainability (such as lower g‐factors), especially at high acceleration factors. Conclusion: It is demonstrated that the joint application of RF and gradient encoding enables SMSlab within a 3D Fourier encoding framework. Images with high isotropic resolution can be reconstructed, and further acceleration is also applicable. The proposed SMSlab 3D k‐space can be valuable for both high‐resolution and high‐efficiency diffusion and functional MRI.